Numerical analysis on the centralization effect of improved horizontal well casing centralizer - Xie, Jinliang; Mu, Zongjie; Liu, Baozhen; Zeng, Changhui; Gong, Yifan (Frontiers in Energy Research, 2023)
Horizontal well technology is a promising method for oil and gas development. During cementing operations in horizontal wells, it was found that conventional casing centralizers could not meet the requirements for casing cementing in expanded wellbores. Therefore, a new type of casing centralizer needs to be designed for horizontal well sections that have undergone enlargement. By analyzing the most common materials currently used, 45 steel was selected for the spring leaf of the novel casing centralizer. To evaluate the centralization effect of the horizontal well casing centralizer, a casing centralization degree evaluation function was established, and a wellbore-centralizer mechanical model was proposed using the finite element method to simulate the working conditions of the centralizer spring leaf in ϕ215.9 and ϕ311.2mm well sections. On this basis, a wellbore-centralizercasing coupling model that does not consider the effect of wellbore fluid on the casing was established to simulate the centralization characteristics of the new casing centralizer and traditional centralizer under different wellbore sizes. Simulation results show that the average casing centralization degree of the new centralizer is 85.53%, while that of the traditional centralizer is 55.58%. That is, the horizontal well casing centralizer can maintain a good centralization effect on the casing string.